The Relationship of Knowledge and Occupation with the Incidence of Anaemia in Pregnant Women - Arnianti Arnianti (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Anaemia is one of the indirect causes of death of pregnant women. Anaemia in pregnancy is a condition where the hemoglobin level of the pregnant women is lower than 11.0 g/dL. The objective of this research was to identify the effect of knowledge and occupation on the incidence of anaemia in pregnancy. Method: The research was conducted in the working areas of the Bara Permai Health Center, Benteng Health Center and Wara Selatan Health Center in Palopo City. This research employed an analytical observational study with a case control study research design. The sampling used a purposive sampling technique. The sample size in this study was 99 samples consisting of 33 cases and 66 controls.Data analysis used univariate and bivariate analysis with chi square test. Finding: The risk factor identified to be related to the incidence of anaemia in pregnancy was knowledge with an Adjusted OR (AOR) = 4.126 (95% CI = 1.574-10.820), with p -value = 0.003 (p<0.05). Meanwhile, occupational factors were found not to be related to the incidence of anaemia in pregnancy. Conclusion: There is a significant influence of the knowledge level on the incidence of anaemia in pregnancy.